A prominent crista terminalis associated with atrial septal aneurysm that mimics right atrial mass leading to atrial arrhythmias: a case report - Bolognesi, Massimo (BioMed Central, 2012)
INTRODUCTION: The crista terminalis is a variant of normal anatomical structures within the right atrium that mimics an atrial mass on a transthoracic echocardiogram. Atrial septal aneurysm is a rare but well-recognized cardiac abnormality of uncertain clinical significance. The association between crista terminalis and atrial septal aneurysm is unusual but not completely casual. Both anatomical heart structures can lead to atrial arrhythmias. CASE PRESENTATION: This case report describes the accidental discovery during an echocardiographic examination of a 64-year-old Caucasian woman who had a left bundle branch block and palpitations. CONCLUSION: The clinical relevance of this anatomical evidence in unknown. This was an occasional finding of transthoracic echocardiography, but in this case it is possible to assume its relationship with the occurrence of atrial arrhythmias, and also that computed tomography scan and cardiovascular magnetic resonance is mandatory to define the structure and function of these incidental findings.